2022
DOI: 10.1002/eco.2514
|View full text |Cite
|
Sign up to set email alerts
|

The study on the comparative responses of aquatic vegetation to the interannual water level variation in different hydrologically connected sub‐lakes based on GEE technology

Abstract: Water level variation is considered as a main controlling environment factor affecting the growth of aquatic vegetation in Poyang Lake, the largest freshwater lake in China. It is significant to study the influences of water level change on aquatic vegetation under various hydrological conditions. Taking the free connected sub-lake Bang Lake and partially controlled sub-lake Dahuchi Lake of Poyang Lake as research objects and based on the cloud computing platform of remote sensing of Google Earth Engine (GEE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Accordingly, those authors concluded that the water-level fluctuation's magnitude is a prominent factor determining the distribution of lake vegetation, followed by relative altitude and submergence duration. Chen et al [17] compared the responses of aquatic vegetation cover to the water level variation for different connected sub-lakes, and found that the aquatic vegetation cover of freely connected sub-lakes were more susceptible to water level variation than partially controlled sub-lakes. All these studies cited above were deterministic quantitative analyses of the relationships between water levels and vegetation based on field-sampled data.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, those authors concluded that the water-level fluctuation's magnitude is a prominent factor determining the distribution of lake vegetation, followed by relative altitude and submergence duration. Chen et al [17] compared the responses of aquatic vegetation cover to the water level variation for different connected sub-lakes, and found that the aquatic vegetation cover of freely connected sub-lakes were more susceptible to water level variation than partially controlled sub-lakes. All these studies cited above were deterministic quantitative analyses of the relationships between water levels and vegetation based on field-sampled data.…”
Section: Introductionmentioning
confidence: 99%